Sindrom iritabilnega črevesa - Dajčman, Davorin (Medicinski razgledi, 2005)
Irritable bowl syndrome is one of the most common medical condition diagnosed today. It is a chronic functional gastrointestinal disorder tha affects all aspects of the patient's daily life. It was recognized nearly two centuries ago, but it still remains widely misunderstood by both patients and physicians. Irritable bowel syndrome has been given a number of different names over the years, including nervous colitis, spastic colitis, mucous colitis, unstable colon and irritable colon. Today it is known that bowel syndrome is a syndrome of findings rather than just a single, isolated complaint that can affect multiple areas of the gastrointestinal tract and is not limited only to the colon. Understanding of the pathophysiology of irritable bowel syndrome has changed considerably during the past 50 years. Initially, it was thought to represent a nervous disorder of the gastrointestinal tract. However, new studies have demonstrated that irritable bowel syndrome is not caused by a single factor; rather, it is a complex disorder in which a number of physiologic processes are involved. These include abnormalities of intestinal motility, alternations in the visceral sensory function and changes in central nervous system processing of sensory information. Today it is believed that the intestinal and the brain are intimately connected and that this connection, often called the brain-gut axis, play a central role in the theory of irritable bowel syndrome. Significant advances in understanding of the pathophysiology of IBS have enabled the medical profession to move forward from a primarily descriptive model to a true biopsychosocial model that treats all its aspects. The aim of this article is to summarize the current status of knowledge about Irritable bowel syndrome, with emphasis on the diagnosis and treatment of this common medical condition.
Keywords: Irritable bowel syndrome; Sindrom iritabilnega črevesa; črevesje; gastrointestinalne bolezni; debelo črevo; disease; bolezni; prebava; motnje